2009
DOI: 10.3390/molecules14010540
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Pharmacological Activities of Squalene and Related Compounds: Potential Uses in Cosmetic Dermatology

Abstract: Squalene is a triterpene that is an intermediate in the cholesterol biosynthesis pathway. It was so named because of its occurrence in shark liver oil, which contains large quantities and is considered its richest source. However, it is widely distributed in nature, with reasonable amounts found in olive oil, palm oil, wheat-germ oil, amaranth oil, and rice bran oil. Squalene, the main component of skin surface polyunsaturated lipids, shows some advantages for the skin as an emollient and antioxidant, and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
211
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(220 citation statements)
references
References 50 publications
3
211
0
6
Order By: Relevance
“…The GC-MS analysis has identified 30 compounds from all the solvent extracts from the L. leucocephala leaves and some of them have been reported to possess many biological properties such as antimicrobial, anticancer, cancer preventive, diuretic, anti-inflammatory, antioxidant; antitumor, antihistaminic, nematicide, pesticide, antiandrogenic, hypocholesterolemic and hepatoprotective as summarized in table 2. [18] Among the identified phytochemicals, squalene is a triterpene that is an intermediate in the cholesterol biosynthesis pathway [19], and it is used in cosmetics as a natural moisturizer [14,17]. Squalene is reported to be an antioxidant activity [17,20,21], anticancer activity [17,22] and chemopreventive activity against colon carcinogenesis [17,23,24].…”
Section: Resultsmentioning
confidence: 99%
“…The GC-MS analysis has identified 30 compounds from all the solvent extracts from the L. leucocephala leaves and some of them have been reported to possess many biological properties such as antimicrobial, anticancer, cancer preventive, diuretic, anti-inflammatory, antioxidant; antitumor, antihistaminic, nematicide, pesticide, antiandrogenic, hypocholesterolemic and hepatoprotective as summarized in table 2. [18] Among the identified phytochemicals, squalene is a triterpene that is an intermediate in the cholesterol biosynthesis pathway [19], and it is used in cosmetics as a natural moisturizer [14,17]. Squalene is reported to be an antioxidant activity [17,20,21], anticancer activity [17,22] and chemopreventive activity against colon carcinogenesis [17,23,24].…”
Section: Resultsmentioning
confidence: 99%
“…It was so called due to its first historical isolation from shark liver oil, where it is contained in large quantities, and is considered its richest source. 65 In humans, about 60 percent of dietary squalene is absorbed and is distributed ubiquitously in human tissues in small amount. 66 Recent in vitro and in vivo model experiments suggest a tumour-inhibiting role for squalene.…”
Section: Squalenoylationmentioning
confidence: 99%
“…Besides the strong affinity to lipophilic compounds, squalene can act as a vital antioxidant to exert cytoprotective effect. 36 Previous studies 14,37 have demonstrated that squalene is efficacious in stabilizing the mammalian cell membrane in cyclophosphamide-and isoproterenol-elicited cardiotoxicity. Even though the cationic squarticles extracted amitriptyline from the highly perfused organs and largely located it in the liver for elimination, this nanosystem did not accomplish the end point of MAP recovery and lethality reduction; this can be associated with the faster release of amitriptyline from the cationic squarticles than from the anionic ones after entrapment.…”
Section: Discussionmentioning
confidence: 99%